Investigating the Role of Experimental Variables in Characterization of Lidocaine Hydrochloride Cubosomes by QbD (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The objective of this research work was to analyze the effect of experimental components (homogenizationtime, speed of homogenization, and time of sonication) on the characterization of cubosomes loaded withLidocaine Hydrochloride (LH). Materials and Methods: The Top-down method was adopted to prepare LHcubosomes using lipid (Glyceryl Monooleate), stabilizer (Poloxamer-407) along with water in varied proportions.32 factorial design was adopted to explain how the two independent factors, that is, homogenization speed andsonication time affect the four responses at varied levels of the processing parameters for the preparation ofdrug-encapsulated cubosomes. Results and Discussion: The most acceptable entrapment capacity was foundat a homogenization speed of 50 rpm and sonication time employed for 10 min for the formulation LT8 withinthe confidence intervals adopted by the 32 factorial design. LT8 was found to have Entrapment efficiency (EE)of 75 percent, Zeta potential of 21.5 mV, vesicle size of 150.3± 0.77 nm, and PolyDispersibility Index of 0.278.As Hominization speed increased there was a noticeable improvement in the characterization of cubosomes,however, enhanced characterization parameters were observed in dispersions prepared with a medium level ofsonication time. Conclusion: A steady dispersion of LH was formed with a high level of speed of homogenizationand a medium level of sonication time to attain the desired parameters for the characterization of cubosomes.Therefore, it is concluded that the speed of homogenization of 50 rpm and sonication time of 10 min resulted ina stable dispersion.